2019
DOI: 10.1002/ajs4.82
|View full text |Cite
|
Sign up to set email alerts
|

Australian employment services: Help or hindrance in the achievement of mutual obligation?

Abstract: The concept of mutual obligation underpins Australian employment services. In return for receiving income support, there are three elements of mutual obligation: to actively seek work; to improve one’s competitiveness in the labour market; and to contribute to the community. Failing to undertake mutual obligation activities results in sanctions, usually unemployment benefit suspension or cancellation. In the year 2017/18, one mutual obligation activity, compulsory employment service provider appointments, acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
(29 reference statements)
2
15
0
Order By: Relevance
“…However, we found little difference in employment outcomes between respondents who were compulsorily or voluntarily engaged with DES. Our findings align with studies critical of ‘Welfare to work’ activation policies, particularly in contexts whereby underlying structural barriers to employment such as discrimination and the limited supply of suitable jobs remain unaddressed [ 39 , 47 , 48 , 49 , 50 , 51 ]. We also question what will happen to excluded voluntary DES participants who are willingly trying to engage with the labour market but need support to do so, particularly given employment plays a vital role in supporting socio-economic and health and well-being outcomes for people with disabilities [ 1 , 4 , 52 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…However, we found little difference in employment outcomes between respondents who were compulsorily or voluntarily engaged with DES. Our findings align with studies critical of ‘Welfare to work’ activation policies, particularly in contexts whereby underlying structural barriers to employment such as discrimination and the limited supply of suitable jobs remain unaddressed [ 39 , 47 , 48 , 49 , 50 , 51 ]. We also question what will happen to excluded voluntary DES participants who are willingly trying to engage with the labour market but need support to do so, particularly given employment plays a vital role in supporting socio-economic and health and well-being outcomes for people with disabilities [ 1 , 4 , 52 ].…”
Section: Discussionsupporting
confidence: 84%
“…This proposed program change requires more analysis of how this may influence employment outcomes, with research demonstrating job-seekers with disabilities feel less well-supported within the mainstream employment program [ 24 , 46 ]. More broadly, the even more stringent mutual obligations placed on mainstream employment participants have been found to undermine the well-being and confidence of participants to actively engage in the program and labour market [ 29 , 39 ]. While this proposed policy change may lead to desired cost-savings for the DES program, it is likely that these savings will be shifted to the mainstream employment program and potentially onto to other systems such as health because of the unintended consequences of participants having to work with providers less skilled in working with people with disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We sought to understand these assumptions further by reanalysing field notes from previous focus group research (O'Halloran et al 2019) on unemployed workers' experiences of Australian employment services and then commissioning additional focus groups specifically to explore the issues of parking and creaming to consider the following questions:…”
Section: Literature Reviewmentioning
confidence: 99%
“…While there is substantial research on the experiences of unemployed workers within marketised employment systems, including the authors' previously reported research (O'Halloran et al 2019), parking and creaming have not been explicitly examined from this perspective. This article reports on research that aims to fill this gap by examining the experiences of unemployed workers who report that they have been parked or creamed by their provider.…”
Section: Introductionmentioning
confidence: 99%